The Thermodynamic Dissociation Constants of the Antidepressant Vortioxetine Using UV-VIS Multiwavelength pH-Titration Data - Meloun, Milan; Pilařová, Lucie; Čápová, Aneta; Pekarek, Tomas (My University, 2018)
Potentiometric and spectrophotometric pH-titrations of the antidepressant Vortioxetine for dissociation constants determination were compared. Vortioxetine is an atypical antidepressant, i.e. a serotonin modulator and stimulator. It was approved by the U.S. FDA for the treatment of major depressive disorders in adults. Depressive disorders are common mental health conditions thought to be caused by an imbalance in serotonin and norepinephrine in addition to multiple situational, cognitive, and medical factors. A chemometrics approach to nonlinear regression of the pH-spectra (REACTLAB, SQUAD84) and pH-titration (ESAB) determined three dissociation constants. A sparingly soluble neutral molecule LH of Vortioxetine was capable of protonation to form the still soluble three cations LH2+, LH32+ and LH43+ in pure water. In the range of pH 3 to 10 three dissociation constants could be reliably estimated from small changes in spectra of 9.2 × 10-5 M Vortioxetine. Although the change of pH somewhat less affected changes in the chromophore, three thermodynamic dissociation constants were estimated pKTa1 = 5.22, pKTa2 = 7.12, pKTa3 = 9.16 at 25°C and pKTa1 = 5.20, pKTa2 = 7.10, pKTa3 = 9.11 at 37°C. Three thermodynamic dissociation constants of 3 ×10-4 M Vortioxetine were determined by the regression analysis of potentiometric titration curves pKTa1 = 5.10, pKTa2 = 8.30, pKTa3 = 9.20 at 25°C and pKTa1 = 5.02, pKTa2 = 8.22, pKTa3 = 9.20 at 37°C. A prediction of the dissociation constants of Vortioxetine was made using the MARVIN and ACD/Percepta programs but only two dissociation constants were theoretically proposed.
Termodynamické disociační konstanty antidepresiva Vortioxetinu s použitím UV-VIS vícenásobné pH-titrace
Keywords: Dissociation constants; Vortioxetine; spectrophotometric titration; REACTLAB; SQUAD84; ESAB; Disociační konstanty; Vortioxetin; pH-spektrofotometrická titrace; REACTLAB; SQUAD84; ESAB